Problems and trends in the nanoindustry development in Russia - N. V. Lomonosova; D. A. Petrusevich (Российский технологический журнал)
In the present paper some special features of the Russian nanoindustry are researched. The object of the research is the nanoindustry that is taken into account as a complex structure of the organisations in the Russian Federation, which develop knowledge-intensive production at the nano scale (1-100 nm) with high added value and unachievable earlier technical features and possibilities for different industries. The main theme of this paper is an observation of the set of factors, which have influence on the future of the nanoindustry in Russia. The main goal of the research is to analyze factors of the nanoindustry development in Russia by means of the methods of the formal logic, induction and deduction and by means of the analysis of the open statistical sources. The research is of immediate interest due to the quick development of the nanoproduct world market. It's quite new and includes a lot of actual scientific results. At the same time the Russian sector is still at the beginning stage of search of potentially valuable results of the knowledge-intensive productions. In the paper the modern state of Russian nanoindustry is presented and is held under investigation. It is compared to the nanoindustries in other countries. The SWOT analysis of the Russian nanoindustry development has been made. The advantages and weaknesses of the Russian nanoindustry are taken into account. The possibilities and threats to the Russian nanoindustry market are described. The conclusions of this research can be used in the long-term and short-term forecasts of the Russian nanoindustry development.